PENGARUH ALOKASI DANA DESA TERHADAP BELANJA DESA DI DESA JELEGONG KECAMATAN KUTAWARINGIN KABUPATEN BANDUNG PERIODE 2014-2017 - Jusuf; Agus Yuliana (JEBS (Journal of Economic and Business Student), 2022)
The research aims to know about the influence of village fund allocation to village expenses at Jelegong Kecamatan Kutawaringin Kabupaten Bandung. The research method used quantitative method and was analyzed with correlation and linier regression.The result of analyzed used correlation that relationship between village fund allocation with village expense is very stronge that is 0,81%. The influence of village fund allocation to village expenses that is 67,07%. from analyzed which have been made providable regression Y = 997.641 + 1.015 Village Fund Allocation. Final conlusion that village fund allocation that very stronge relationship to village expenses with contribution influence is stronge. And may it happen village fund allocation can used it well appropriate for overall aim from distribution fund this.